2021
DOI: 10.1177/23779608211029067
|View full text |Cite
|
Sign up to set email alerts
|

Older and Wiser? The Need to Reexamine the Impact of Health Professionals Age and Experience on Competency-Based Practices

Abstract: Introduction Delivery of healthcare services makes up a complex system and it requires providers to be competent and to be able to integrate each of the institute of medicine’s (IOM) 5 core competencies into practice. However, healthcare providers are challenged with the task to be able to understand and apply the IOM core competencies into practice. Objective The purpose of the study was to examine the factors that influence health professional’s likelihood of accomplishing the IOM core competencies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…There are several potential explanations for this. One is that new GPs are more eager to learn about navigating the health care system and are more comfortable to use novel software [40,41]. Whereas, more experienced GPs, accustomed to a certain referral pattern for lung cancer for many years did not feel the need to change routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential explanations for this. One is that new GPs are more eager to learn about navigating the health care system and are more comfortable to use novel software [40,41]. Whereas, more experienced GPs, accustomed to a certain referral pattern for lung cancer for many years did not feel the need to change routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this relationship could not be determined from our data. Xu et al [ 36 ] also identified age and experience as relevant factors when they evaluated health professionals’ engagement with the core competencies defined by the Institute of Medicine (U.S.). However, they found that 18 to 34-year-old health professionals were more likely to provide patient-centered care than their 35 to 65+-year counterparts.…”
Section: Discussionmentioning
confidence: 99%